PROSES INKULTURASI LITURGI DI INDONESIA - E.P.D. Martasudjita (Studia Philosophica et Theologica, 2010)
The problem of the process of liturgical inculturation has a special urgency today in Indonesia, since many practices of liturgical inculturation in some catholic parishes tend to be spontaneous, experimental, and so relying on the good will to contextualize celebration of liturgy in their local culture. In this article the author tries to show how the process of liturgical inculturation should be done. The process of liturgical inculturation is always dialectical, given that it demands a reciprocal dialogue between faith and culture. There are some factors to be noticed for achieving a good process of the liturgical inculturation, that are historical factor of the liturgical inculturation in the Church, some criterias of a right and good liturgical inculturation, and the methods of liturgical inculturation. At the end the author shows some challenges of the process of liturgical inculturation in the Catholic Church in Indonesia.